Source mechanisms and focal depths of East African earthquakes using Rayleigh-wave inversion and body-wave modelling - Shudofsky, Gordon N. (Geophysical Journal of the Royal Astronomical Society, 1985)
The source mechanisms and focal depths of 23 African earthquakes, most of them associated with the East African rift system, have been accurately determined using Rayleigh-wave inversion and body-wave modelling techniques. In so doing we have demonstrated the viability of applying these techniques to intermediate-sized earthquakes in regions of relatively sparse seismicity but high tectonic interest. Earthquake source mechanisms in East Africa are mostly of the normal faulting type. Least compressive stress axes for the events considered exhibit a consistent orientation normal to the rifting trends over a wide region of both the eastern — and western branches of the rift system as well as in seismically active but currently unrifted regions to the south. The mechanisms indicate that the stress system responsible for the current rift faulting is still operative and that the East African rift system may be actively continuing southwards. The length scale of relative homogeneity over which we can use phase velocities determined using a well-constrained reference event or events to retrieve the complex spectra of a neighbouring event is at least 500–600 km for several regions of the East African rift system. The implication is that the Rayleigh-wave travel paths through Africa are largely stable and that lateral heterogeneity in East Africa is not as great as might have been expected in a complex zone of continental rifting. The mechanisms of three events in southernmost Africa show this region to be under relative E–W compression, in contrast to the rifted regions to the north which are subject to general E–W tension. Many of the East African events studied have well-constrained focal depths of 15–30 km, depths that are unusually deep for a region of continental extension if lithospheric thinning by the relative upward movement of asthenosphere is the process responsible for rifting. The consistency of focal mechanisms and tensional stress axis orientations for East African earthquakes having widely ranging epicentres and focal depths suggests that a large-scale process is involved in the continental rifting of East Africa. The results of this study are consistent with the idea that rifting in East Africa is connected with passage of the East African lithosphere over a linear thermally anomalous region in the underlying mantle. It is shown that this idea can also account for many of the temporal and spatial aspects of the East African rift system.